1998
DOI: 10.1021/jp9724075
|View full text |Cite
|
Sign up to set email alerts
|

Photooxidation of Trichloroethylene on Pt/TiO2

Abstract: The gas-phase photooxidation of trichloroethylene (TCE) on Pt/TiO2 has been investigated. The wavelength dependence of this reaction on Pt/TiO2 shows that the addition of small amounts of platinum (≤2%) to TiO2 can enhance the photooxidation of TCE to much longer wavelengths. This result correlates with Maxwell−Garnett calculations and experimental absorption curves for Pt/TiO2 samples. Although the spectral response of Pt/TiO2 extends to longer wavelengths, Pt/TiO2 is found to be less effective in the photoox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(80 citation statements)
references
References 37 publications
6
74
0
Order By: Relevance
“…Similar absorption spectra for Pt-TiO 2 were obtained and discussed in other work. 19,20 Belloni et al reported that the absorption properties of platinized TiO 2 depend on the optical properties of the metal, the matrix and the volume fraction of the metal in the nanocomposite. 19 In their work, the absorption in the visible region of Pt-TiO 2 , with 1% Pt, reached more than 30% of the intensity at the maximum.…”
Section: Resultsmentioning
confidence: 99%
“…Similar absorption spectra for Pt-TiO 2 were obtained and discussed in other work. 19,20 Belloni et al reported that the absorption properties of platinized TiO 2 depend on the optical properties of the metal, the matrix and the volume fraction of the metal in the nanocomposite. 19 In their work, the absorption in the visible region of Pt-TiO 2 , with 1% Pt, reached more than 30% of the intensity at the maximum.…”
Section: Resultsmentioning
confidence: 99%
“…It was proposed that the defect sites (Ti 3+ ) which are necessary for the oxidation of CO to CO 2 was preferentially blocked by Pt particles which reduces the photoreactivity of the catalyst. Pt deposited TiO 2 is also reported to be less effective in the photooxidation of gasphase TCE under broad-band irradiation ( > 300 nm) compared to TiO 2 [53]. [56].…”
Section: Photocatalytic Activity Of Platinum Deposited Titania (Pt/timentioning
confidence: 99%
“…[1][2][3][4][5] The main drawbacks of low quantum yields and the lack of visible light utilization, however, hinder its practical application. To handle these problems, numerous studies have recently been performed to enhance the photocatalytic efficiency and visible light utilization of TiO 2 , which include impurity doping, [6][7][8][9] metallization, [10][11][12][13][14][15] and sensitization. 16,17 According to these published works, the deposition of the metal on visible light catalysts highly improved its photoefficiency through the Schottky barrier CB electron trapping and consequent longer electron-hole pair lifetimes.…”
Section: Introductionmentioning
confidence: 99%